Management of Dental School During the COVID-19 Pandemic: Application of Intervention Mapping - Heidari, Ali; Miresmaeili, Amirfarhang; Poormohammadi, Ali; Bashirian, Saeid; Meschi, Marjaneh; Karkehabadi, Hamed; Baharmastian, Bahareh; Aziziansoroush, Omid; Rabienejad, Nazli; Shirahmadi, Samane (Frontiers in Public Health, 2021)
Background: COVID-19 outbreak has led to the suspension of the activities of dental schools. Therefore, reorganizing clinical setting and supporting services as quickly as possible has received much attention in order to reopen dental schools. The present study aimed to evaluate the applicability of Intervention Mapping (IM) approach for designing, implementing, and evaluating an intervention program to prevent and control COVID-19 in dental schools. Methods: Following the IM protocol, six steps were completed in the planning and development of an intervention, targeting and management of Dental School during the COVID-19 pandemic. Results: The information obtained from the needs assessment revealed that the COVID-19 outbreak prevention was associated with the use of personal protective equipment by all target groups, infection control measures taken in the environment, preparation of the environment and equipment, changes in the treatment plan according to the COVID-19 pandemic, changing the admission process of patients, and reduction of target groups’ attendance in the school are linked with. In this study, determinant factors affecting COVID-19 prevention at the individual level were identified based on the Protection Motivation Theory (PMT). In this program, various methods such as presentation of information, modeling role, and persuasion measures were utilized and the practical programs included educational films and group discussions implemented. Conclusions: Our findings indicated that intervention in dental environments on the basis of IM process can develop a comprehensive and structured program in the dental school, and hence can reduce the risk of COVID-19 infection.